Gender moderates the association between psychopathic traits and aggressive behavior in adolescents. (May 2016) - Orue, Izaskun; Calvete, Esther; Gamez-Guadix, Manuel
Abstract: The aim of this study was to analyze the relationships between psychopathic traits and aggressive behavior in adolescents. We assessed four subtypes of aggression (proactive-overt, reactive-overt, proactive-relational and reactive-relational). Gender was included as a moderator of those relationships. The sample comprised 765 adolescents (464 girls) who completed measures of psychopathic traits (callous–unemotional, grandiose–manipulative and impulsivity) and aggression at Time 1 and one year later. Participants were between 14 and 18 years old. Results showed that callous–unemotional (CU) traits predicted proactive-overt and proactive-relational aggression. Grandiose–Manipulative (GM) predicted proactive-overt and reactive-overt aggression, and Impulsivity-Irresponsibility (II) predicted reactive-overt aggression. The path from CU traits to proactive-overt aggression was higher in girls, and the path from GM to proactive-overt aggression was higher in boys. Results indicate that research on psychopathic traits needs to include both girls and boys to identify gender-specific manifestations of these traits. Highlights: We evaluated in a short term longitudinal study psychopathic personality traits and aggression in 765 adolescents. Different forms and functions of aggression were combined. Psychopathic traits were differently related to different types of aggression. Gender moderated the relationships between psychopathic traits and different types of aggression.